Polymeric Drug Delivery Approaches for Colon Targeting: A Review - Kaur, Apninder; Kaur, Amarjeet; P. Kaur, Vishav; Kaur, Manpreet; Murthy, R.S.R. (Drug Delivery Letters, 2014)
Colorectal cancer being a life style disease, number of cases is increasing day by day. Oral drug delivery to treat colonic diseases encounters many problems like drug stability in the harsh environment of the upper GI tract, low percentage of drug remained in the dosage form to be released in the colon, heavy dilution of the drug released in the colon fluid etc. Hence novel strategies for colon targeting has attracted significant attention during the past 20 years in providing several therapeutic advantages particularly for drugs that are sensitive to acidic condition and to intestinal enzymes. Sustained colonic release of drugs can be useful in the treatment of nocturnal asthma, angina and arthritis while site specific release strategy is needed for local action for conditions involving colonic pathologies, such as ulcerative colitis, colorectal cancer, Crohn's disease and colon cancer. This article is focused on different polymeric materials particularly of natural origin that are considered to design different types of colon delivery systems and their comparative efficacies are discussed.
Keywords: natural polymers